2002
DOI: 10.1114/1.1484220
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Dilated Human Ascending Aorta

Abstract: Dilation of the ascending aorta, associated with Marfan Syndrome, bicuspid aortic valve, or advanced age, may lead to aortic dissection and rupture. Mathematical models can be used to assess the relative importance of increased wall stresses and decreased strength in these mechanical failures. To obtain needed inputs for such models, mechanical properties of dilated human ascending aorta were measured in vitro. Specimens for opening angle, biaxial elastic, and uniaxial circumferential strength tests were cut f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
161
1
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(198 citation statements)
references
References 36 publications
24
161
1
5
Order By: Relevance
“…Additionally, Pham et al found BAV patients, which have been structurally and mechanically linked to MFS patients (13,14,23), to have significantly more isotropic aortic tissue than other AsAA patients, as also found in MFS patients in the current study (24). Pham also found a trend of age-related thickening in BAV tissue, agreeing with our MFS findings.…”
Section: Aneurysmal Stiffeningsupporting
confidence: 82%
See 2 more Smart Citations
“…Additionally, Pham et al found BAV patients, which have been structurally and mechanically linked to MFS patients (13,14,23), to have significantly more isotropic aortic tissue than other AsAA patients, as also found in MFS patients in the current study (24). Pham also found a trend of age-related thickening in BAV tissue, agreeing with our MFS findings.…”
Section: Aneurysmal Stiffeningsupporting
confidence: 82%
“…Significant effort has been devoted to the investigation of the mechanical properties and pathogenesis of AsAA tissue (7,13,14,(18)(19)(20)(21); however, MFS-specific studies are scarce. A number of in vivo studies on Marfan tissues investigate aortic distensibility, stiffness index, and pulse wave velocity (3,(8)(9)(10)(11)(12), consistently finding increased aortic diameter (12), decreased distensibility (8)(9)(10), and stiffness (8,9,12) in MFS patients compared to age-and gender-matched controls; however, these parameters were not correlated, as also found in our study.…”
Section: In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous work investigating the material symmetry of aorta has been performed on animal tissue or involved uniaxial tensile testing, which is unable to conclusively assess the anisotropic response of this tissue. There has been very little published work involving the biaxial experimentation of human aortic tissue, 45,46 and none for AAA tissue. Biaxial tensile testing of AAA recently completed by our laboratory has demonstrated that aneurysmal formation is associated with an increase in circumferential stiffness (830Ϯ120 N/cm 2 versus 330Ϯ60 N/cm 2 for the AAA and AA, respectively [Pϭ0.03]).…”
Section: Ex Vivo Tensile Testingmentioning
confidence: 99%
“…In biaxial loading, tissue is stiffer and its nonlinearity is less (Dixon et al, 2003). Therefore, biaxial and planar tests may be good alternatives to reach a better understanding of arterial behavior (Guccione et al, 1991;L'italien et al, 1994;Okamoto et al, 2002;Sun et al, 2003, Lu et al, 2005Criscione et al, 2005). Simulations of tissues mechanical behavior are applicable for diagnostic and treatment purposes as well as in surgery (Dumoulin & Cochelin, 2000;Gourisankaran & Sharma, 2000;Laroche & Delorme, 2006;Kiousis et al, 2007;Wu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%